Strategi Penguatan Nilai Agama dan Moral melalui Sentra IMTAQ di KB Talia Insan Mulia - Imrotul Ummah; Muhammad Turhan Yani; Achmad Sya’dullah (Institut Nalanda, 2024)
In the process of children's education, strengthening religious morals is very important to shape good character and behavior. This research discusses strategies for strengthening religious morality through the Imtaq center at KB Talia Insan Mulia. How this program helps children understand and practice religious and moral values, and how teachers and parents can work together to improve children's religious and moral values. we will explain how this can be fostered. The approach used in this research is a qualitative approach, the data collection method used in this research. 1) observation 2) interviews, and 3) documentation to investigate findings that actually occur in field and record them systematically as symptoms that appear in research subjects. The strategy of strengthening religious and moral values ​​at KB Talia Insan Mulia is carried out through the Imtaq Center, by providing knowledge about God and religion (Practice of Worship, giving alms, commemoration of religious holidays), good habits by providing examples/examples, getting used to good manners and behavior as well as collaboration between teachers and parents. So that the strengthening of religious and moral values ​​will continue through habituation both at school and at home.